Retail Price Levels and Concentrations of Wholesalers, Retailers and Hypermarkets - Marcus Asplund; Richard Friberg (Sveriges Riksbank, 1999)
This paper examines retail grocery price levels with a very large (unbalanced) panel of stores that operate in well-defined local markets. We explain price variation across grocery retailers by the concentration of wholesalers and retailers, and the market share of hypermarkets (and control for a number of store and region specific factors). Our most important result is that concentration at the wholesale level is an important determinant of retail prices. The price effect of retail concentration and hypermarket market share are statistically significant but small in conomic terms.
Keywords: D43; L13; L81; 330; Firm concentration; market structure; price competition; grocery retail; grocery wholesale